Facilitators of medication adherence in patients with hypertension: a qualitative study - Zahra Ghaderi Nasab; Hamid Sharifi; Hamid Sharifi; Parvin Mangolian Shahrbabaki (Frontiers Media S.A., 2024)
Hypertension has been identified as the most important risk factor for disability and premature death worldwide. This study aimed to explain the factors that facilitate medication adherence from the perspective of patients with hypertension in southeastern Iran. This qualitative study used conventional content analysis and purposive sampling methods to achieve data saturation, involving 25 participants. Facilitating factors were categorized into two main categories: individual and family factors and organizational support. Individual factors included motivational fears, disease acceptance, healthy lifestyle, disease monitoring, and follow-up. Family factors included family support, while organizational support included governmental support to provide inexpensive medicines, comprehensive healthcare team support, health insurance access, and media training. These factors were identified as essential facilitators that significantly influence appropriate adherence to hypertensive drugs. This study revealed that various factors affected medication adherence in these patients, and efforts should be made to improve hypertension treatment and increase medication adherence. Measures taken to control hypertension are cost-effective to reduce the burden associated with this disease. The findings of this study can be valuable in formulating policies for the treatment and care of hypertension.